Functional Data Analysis of Payment Systems - Laukaitis, A.; Račkauskas, A. (Nonlinear Analysis: Modelling and Control, 2002)
In this paper for a credit cards payment system as robust predictor of transactions number and transactions intensity is proposed by means of functional autoregressive model. Intraday economic time series are treated as random continuous functions projected onto low dimensional subspace. Both B-splines and Fourier bases are considered for data smoothing.
Keywords: high frequency data; functional AR model; functional data analysis; B-splines; Fourier bases; credit cards payment system